Physical therapy of patients after cerebral ischemic stroke from the standpoint of a patient-centered approach - Malyarova, Y.M.; Rudenko, A.M.; Zviriaka , O.M.; Kuksa, N.V. (Medicni Perspektivi, 2024)
Acute cerebrovascular accident remains an important medical and social problem. An important area of intensification of rehabilitation care for patients after cerebral ischemic stroke is the using of a patient-centered approach, which is often associated with increased patient satisfaction and adherence to rehabilitation. The aim of the study was to balance the restoration of physical and functional capabilities of patients after cerebral ischemic stroke in the post-acute rehabilitation period using a patient-centered approach. A program of physical therapy for patients after cerebral ischemic stroke in the post-acute rehabilitation period was implemented from the standpoint of a patient-centered approach in accordance with the defined goals of rehabilitation intervention. The study included 37 patients, 22 men and 15 women with post-stroke muscle spasticity who were under a nine-month follow-up during the second stage of rehabilitation in the post-acute rehabilitation period. The average age of men was 52.1±8 years, the average age of women was 50±13 years. A comparative evaluation of the effectiveness of the physical therapy program was conducted, based on examination methods in accordance with the International Classification of Functioning, Disability and Health. At the end of the experimental study, the following changes in patients after cerebral ischemic stroke were found: decrease in the intensity of pain in the muscles of spastic limbs according to the visual analog pain scale by 12.9±1.02 points (p<0.05); decrease in the severity of motor deficit by an average of 1.7±1.0 points (p<0.05) according to the Motor Deficit Scale (Medical Research Council); the index of muscle tone of the adductor muscles of the shoulder decreased by 0.9±0.4 points (p<0.05), the muscles of the forearm flexors by 0.4±0.2 (p<0.05) points on the Ashworth Scale (Modified Ashworth Scale); assessment of motor function of the affected limb showed an increase in motor activity by 15±0.4 points (p<0.05), before physical therapy the index was 29±0.2 points (p<0.05), and after it – 44.3±0.8 points (p<0.05) on the Action Research Arm Test scale; statistical improvement in self-care and functionality in patients by 1.2±0.1 points (p<0.05) on the Modified Rankin Scale; the average walking and mobility score in patients increased by 3.7±0.1 points (p<0.05) on the Rivermead mobility index. The results of the experimental study confirmed that the algorithm and content of the physical therapy program from the standpoint of a patient-centered approach were effective for patients who had suffered a cerebral ischemic stroke; this indicates the possibility and feasibility of their further using for post-stroke patients in the post-acute rehabilitation period.